2004
DOI: 10.1111/j.1365-2133.2004.06075.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and glycosylation of MUC1 in epidermolysis bullosa-associated and sporadic cutaneous squamous cell carcinomas

Abstract: The results demonstrate that a significant proportion of DEB/JEB and sporadic SCCs express MUC1 in > 50% of tumour cells. Therefore, MUC1 may be a suitable candidate antigen against which to develop a tumour vaccine for these patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In cutaneous squamous cell carcinoma (both sporadic and that associated with epidermolysis bullosa) and Bowen’s disease, the tumor cells express a hyperglycosylated form of MUC1 (identified with glycosylation status specific antibodies). [27] This altered glycosylation of mucins, chiefly hyperglycosylation, has been suggested as a possibly mechanism used by tumor cells to avoid detection by the immune system possibly by masking of the peptide epitopes, thus contributing to their continued survival. The importance of MUC1 in the immune response pathway is further confirmed by its ability to modulate the adhesion of intramural polymorphonuclear leucocytes to the epithelium in vitro .…”
Section: Functions Of Mucins In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In cutaneous squamous cell carcinoma (both sporadic and that associated with epidermolysis bullosa) and Bowen’s disease, the tumor cells express a hyperglycosylated form of MUC1 (identified with glycosylation status specific antibodies). [27] This altered glycosylation of mucins, chiefly hyperglycosylation, has been suggested as a possibly mechanism used by tumor cells to avoid detection by the immune system possibly by masking of the peptide epitopes, thus contributing to their continued survival. The importance of MUC1 in the immune response pathway is further confirmed by its ability to modulate the adhesion of intramural polymorphonuclear leucocytes to the epithelium in vitro .…”
Section: Functions Of Mucins In Health and Diseasementioning
confidence: 99%
“…Lymphocytes present in the normal skin reacted specifically with an antibody (mAb SM-3) that recognizes the hypoglycosylated form of MUC1. [27] Merkel cells present in the normal epidermis and hair follicles were immunolabeled by antibodies that recognized the underglycosylated (mAb BM-7) or unglycosylated (mAb BM-2) forms of MUC1 as well as those that were not specific for its glycosylation status (VU-2G7). [35] Using these antibodies, the acinar elements of both the sweat and sebaceous glands were brightly positive, while the ductal cells were uniformly negative.…”
Section: Expression Of Mucins In the Normal Skinmentioning
confidence: 99%
“…Previous studies have failed to identify consistent differences between RDEB cSCC and cSCC from the general population or organ transplant recipients in spite of the different clinicopathologic behavior. In fact, in virtually all studies to date, RDEB cSCC exhibit similar characteristics to non-RDEB cSCC and a causative relationship with tumor progression has yet to be unequivocally identified (7)(8)(9)(10)(11)(12)(13)(14)(15). With few exceptions these studies have focused on tumor keratinocytes and have ignored the surrounding stroma.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical data would suggest defined pathology unique to RDEB SCC yet numerous molecular and histological studies identify only similarities with UV induced cSCC in the general population (Tyring et al, 1989;Arbiser et al, 1998;Arbiser et al, 2004;Cooper et al, 2004;Mallipeddi et al, 2004;Kivisaari et al, 2008;Purdie et al, 2010) and those which report differences are neither replicated nor significantly powered to make definitive conclusions Ortiz-Urda et al, 2005). To date no single study has identified a distinct difference in the histology or expression of markers both at the mRNA or protein level when comparing cSCC from RDEB patients with cSCC in the general population.…”
Section: Are There Differences Between Rdeb Scc and Non-rdeb Scc?mentioning
confidence: 99%
“…Another cSCC specific marker, which has been suggested to be involved in RDEB tumourigenesis, is mucin-1. This marker is found in all RDEB SCCs (n=25), JEB SCC (n=5) and 52 of 55 UV induced cSCCs (Cooper et al, 2004).…”
Section: Matrix Metalloproteinase Expression In Rdebmentioning
confidence: 99%